KNOWLEDGE AND ATTITUDE OF MOTHERS ON RISK FACTORS INFLUENCING PREGNANCY OUTCOMES IN ABEOKUTA SOUTH LOCAL GOVERNMENT AREA, OGUN STATE - Eni-Olorunda, Tolu; Akinbode, Olusola Otito; Akinbode, Ayobami Oluwaseun (European Scientific Journal, ESJ, 2015)
Pregnancy outcomes rank among the most pressing reproductive health problems in the world. Factors influencing pregnancy outcomes may include poor nutrition of the woman, child spacing, maternal age (under 15 years and beyond 35 years), inadequate prenatal care, lifestyle behaviours, such as; smoking, alcohol consumption, drug abuse, overweight, obesity and poverty The study investigated knowledge and attitude of mothers on risk factors influencing pregnancy outcomes in Abeokuta South Local Government Area of Ogun State. One hundred mothers were randomly selected and participated in the study. Descriptive research design was adopted. The instrument used to elicit responses from the respondents was a well-structured questionnaire designed by the researchers. Data was analysed using descriptive statistics such as frequency counts and percentages. Findings showed that only a few mothers 37(37.8%), have knowledge that being pregnant at age 35 years and above could result in giving birth to babies with developmental disabilities such as Down Syndrome. Majority of the mothers 74(75.5%) however are knowledgeable about malnutrition as a risk factor in pregnancy. The attitude of the mothers as revealed in this study showed that majority 59(59.6%) do not see anything wrong in being pregnant on yearly basis. It was therefore recommended that pregnant mothers should see the need for early antenatal care. They should also avail themselves opportunities of attending programmes that would further aid their knowledge and have a change of attitude on risk factors that can influence pregnancy outcomes.